Business expansion and structural change in pre-war China : Liu Hongsheng and his enterprises, 1920-1937 - Chan, Kai Yiu (Business, Innovation & Society in Asia., 2006)
This book examines the relationship between business expansion and the structure of business in pre-war China through a careful and pioneering study of the enterprises of Liu Hongsheng during the 1920s and 1930s.